2011
DOI: 10.1111/j.1464-410x.2011.10177.x
|View full text |Cite
|
Sign up to set email alerts
|

Increased incidence of Leydig cell tumours of the testis in the era of improved imaging techniques

Abstract: Study Type – Diagnostic (exploratory cohort) Level of Evidence 2b What’s known on the subject? and What does the study add? Leydig cell tumours (LCTs) of the testis are rare tumours, accounting for 1–3% of all testicular neoplasms. Our data indicate that using scrotal ultrasound with high resolution imaging in routine checkups leads to an earlier detection of LCTs. Most patients underwent an organ‐sparing surgery and no androgen deprivation was observed. OBJECTIVE • To report an observed high frequency of Leyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
43
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(48 citation statements)
references
References 33 publications
2
43
0
3
Order By: Relevance
“…MRI can detect small non-palpable LCTs otherwise not visible on ultrasonography 10. On ultrasonography, LCTs usually appear as a non-homogeneous hypoechoic testicular nodule with peripheral hypervascularity and minimal internal colour Doppler flow 11.…”
Section: Discussionmentioning
confidence: 99%
“…MRI can detect small non-palpable LCTs otherwise not visible on ultrasonography 10. On ultrasonography, LCTs usually appear as a non-homogeneous hypoechoic testicular nodule with peripheral hypervascularity and minimal internal colour Doppler flow 11.…”
Section: Discussionmentioning
confidence: 99%
“…Leydig cell tumors are being discovered more frequently as testicular ultrasound is performed for indications other than palpable testicular mass [21]. Leydig cell tumors often demonstrate homogeneous hypoechoic echo texture similar to that of seminoma; smaller size (usually <1 cm) and a characteristic ‘halo’ of Doppler vascular flow surrounding the periphery of the tumor are clues to their identification [22].…”
Section: Discussionmentioning
confidence: 99%
“…1 The majority of these tumours occur between the ages of 20-60 years and most commonly present with painless testicular enlargement or a palpable mass. 2 Though uncommon, patients can present symptomatically. Symptoms from excessive hormone secretion, such as gynecomastia, can be seen in up to 15% of adults with Leydig cell tumours, though Sertoli cell tumours are rarely symptomatic.…”
Section: Introductionmentioning
confidence: 99%
“…1,9 Other studies have reported higher rates of metastatic disease, with Bertram et al reporting a 20% rate of metastatic disease at the time of diagnosis and a 40% risk of metastatic involvement within two years of diagnosis. 10 Furthermore, malignant SCSTs have been reported to respond poorly to conventional radiotherapy and cytotoxic Lindsay M. Yuh, MD 1,5 ; Primo N. Lara Jr, MD 2,5 ; Rebecca M. Wagenaar, MD 1,5 ; Christopher P. Evans, MD 1,5 ; Marc A. Dall'era, MD 1,5 ; Rosemary Cress, MD 3,4,5 ; Stanley A. Yap, MD A contemporary population-based study of testicular sex cord stromal tumours: Presentation, treatment patterns, and predictors of outcome scsT: Detection and intervention chemotherapy. Controversy remains as to the recommended treatment due to a lack of evidence-based data.…”
Section: Introductionmentioning
confidence: 99%